ANALYSIS OF THE EFFECT OF FOREIGN JOINT STOCK PRICE INDEX ON INDONESIAN COMBINED STOCK PRICE INDEX WITH UNITED STATES DOLLAR AS A MODERATING VARIABLE - mie, mie (International Journal of Public Budgeting, Accounting and Finance, 2018)
The purpose of this study was to determine and analyze the effect of the All Ordinaries AustraliaIndex (A ORD ) , the FTSE 100 Index(FTSE 100) , Nikkei 225(N225) , Shanghai Composite Index(SSEC) , and Dow JonesIndex (DJI A ) towards the Jakarta Composite Index( JKSE ) both simultaneously and partially with US Dollar Exchange Rate as a moderatingvariable . This research is a descriptive qualitative research. Population tand samples used in this study were 102 of observational data from the Composite Stock Price Index are listed on the Indonesia Stock Exchange, the Australian Stock Exchange, London Stock Exchange, Tokyo Stock Exchange, Shanghai Stock Exchange and New York Stock Exchange during the period January 2008 to Juni 2016. The sampling technique used was saturated samples, thus the total observations were also 102 data . The data analysis method used is multiple linear regression and residual analysis. The test results prove that simultaneous, AORD Index, the FTSE 100 Index, Index .N225, SSEC index and DJIA index significant effect on JKSE. But partially, only AORD index significantly influence JKSE, while the FTSE 100 Index, Index .N225, SSEC index and DJIA index has no effect on JKSE. And the USD exchange rate is not a variable that can moderate the relationship between AORD, FTSE 100, N225, SSEC, and DJIA with JKSE.